Management of complications after tension-free midurethral slings - (:unkn) unknown (My University, 2013)
Since their introduction in 1996, tension-free midurethral slings (MUS) have been pro-ven to have long-term efficacy and safety. They are considered the gold standard treat-ment of female stress urinary incontinence, especially in cases that are associated with urethral hypermobility. However, they are not free of complications and, although rare, some of these complications can be challenging for both patients and physicians. Some complications occur intraoperatively, whereas others appear in the early or late post-operative period. There is less controversy in the diagnosis and treatment of complica-tions such as vaginal extrusion or urinary system erosion, whereas de novo voiding prob-lems are at best not completely understood. Voiding dysfunction after MUS placement may vary in a wide range from urinary frequency or urgency to retention and is usually attributed to the obstructive or irritative effect of the sling. However, present urody-namic criteria for the diagnosis of female infravesical obstruction are not satisfactory, and the best management policy for de novo voiding dysfunction remains controversial. In the majority of cases, the diagnosis of obstruction leading to a urethral release sur-gery depends on a combination of several clinical findings. The timing of urethral re-lease surgery varies depending on the preferences of the surgeon, and the outcome of this surgery is not always predictable. The purpose of this review was to assess the diag-nosis and management of the immediate, short-term, and long-term complications of MUS in light of the current literature in an attempt to determine the best management policy. © The Korean Urological Association, 2013.
Keywords: Complication; Midurethral sling; Stress urinary incontinence